ANALISIS SINGLE EXPONENTIAL SMOOTHING UNTUK MEMPREDIKSI PENJUALAN AYAM - Dede Irma Suryani; MOH. SIDDIK; MHD IHSAN (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Basically an increase in sales means an increase in sales which is a positive thing for a company, but it will be a problem if the company does not have sufficient product inventory to meet consumer demand. Forecasting is the art and science of predicting future events. Forecasting will involve taking historical data (such as last year's sales) and projecting it into the future using mathematical models. The Single Exponential Smoothing method is a method that has different weighting techniques for the available data. PHP is a programming language that is intended to create web-based applications, and MySQL is the first database supported by a script programming language for the internet php. Therefore, the application of forecasting techniques for the cases experienced by Syahbana Group 2 is the best solution. By utilizing forecasting techniques using the Single Exponential Smoothing method and also using the PHP programming language and mysql database, it is expected to be able to monitor the development of broiler sales in Syahbana Group 2. The results of this study prove that the application of the Single Exponential Smoothing method in forecasting broiler sales makes it easier for Syahbana Group 2 because the forecasting system provides a good accuracy value in providing sales planning for the following month